Government Hospitals lease contract for the private sector In Iraqi law - المخزومي, وليد مرزة; محمد, شهد حسين (Journal of Legal Sciences, 2019)
The contract for iease public hospitals to the private sector is one of the administrative contracts in which all the elements of the administrative contract are available. It is signed by the administration represented by the Minister of Health. It is presented to a public hospital which is one of the public facilities that provide medical services. The Ministry of Health may also apply to the Leased Hospital. It may also amend the contract in accordance with the public interest, in addition to the possibility of dissolving the contract without recourse to the courts in case the tenant violates the terms of the contract, The State resorted to it in the event that it is unable to provide medical services within the required range, as it is one of the most important services that must be provided continuously, so the State resorts to providing advanced medical services of high quality by the private sector.      So we call on the Iraqi legislator to activate the decision Revolutionary Command Council No. (162) for the year 1990 on leasing government hospitals to the private sector, especially after the financial crisis experienced by Iraq, which directly affected the provision of medical services to citizens, where the private sector to help provide advanced medical services.